Behavior of glass and carbon FRP tube encased recycled aggregate concrete with recycled clay brick aggregate. (1st November 2016) - Gao, Chang; Huang, Liang; Yan, Libo; Kasal, Bohumil; Li, Wengui
Abstract: In literature, there are few studies which investigated compressive behavior of fibre reinforced polymer (FRP) tube confined recycled aggregate concrete (RAC) where the recycled aggregates (RAs) mainly came from demolished old concrete components. Study which considered FRP tube confined RAC using recycled clay brick aggregates (RCBA) originating from demolished brick masonry components is rare. Thus, this paper reports a systematic study on axial compressive behavior of FRP tube encased RAC containing RCBA (termed as FRP-confined RAC-RCBA). The experimental variables considered are, i.e., replacement ratio of RCBA ( r = 0, 50, 70 and 100%), FRP tube thickness ( n f = 2, 4 and 6 layers) and type of fibre material (GFRP and CFRP). This study shows that both GFRP and CFRP tubes enhanced strength and deformation of the confined RAC-RCBA specimens remarkably. The ultimate compressive stress of the confined specimens decreased with an increase of RCBA replacement ratio but their axial deformation kept approximately constant. Failure mode and the compressive stress-strain behavior of G/CFRP-confined RAC-RCBA were similar to these tube confined normal aggregate concrete (NAC) and the ultimate compressive strength of G/CFRP tube confined RAC-RCBA specimens enhanced with an increase in FRP tube thickness. The CFRP-confined specimens showed higher ultimate strength but lower ultimate axial strain than those of GFRP-confined specimens. The applicability of eight widely used confinement models, i.e., 5 design-oriented and 2 analysis-oriented models, for FRP-confined NAC to FRP-confined RAC-RCBA was also evaluated.